SISTEM INFORMASI GEOGRAFIS BERBASIS WEB DAERAH IRIGASI BATANG ALAI SELATAN KABUPATEN HULU SUNGAI TENGAH - Wibawanto, Arif Eko; Sobatnu, Ferry; Ramadaniaty, Juwita (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2020)
Irrigation network is one of the infrastructure needed in an effort to improve the quality and quantity of agricultural production. This can not be separated from the conditions of good irrigation channels and proper maintenance. In the construction process of the Batang Alai Selatan irrigation area which is the purpose of the construction of the D.I irrigation network information system in South Batang Alai In the form of a website that can be accessed online. This study uses 2 data collection methods, namely: primary obtained from the results of tracing irrigation networks taking coordinates of buildings and channels using GPS Map directly in the field, and secondary data obtained from data sourced from official documents from relevant agencies. From the 2 data, the writer can build an Online Information System for D.I Batang Alai. The results of this research are in the form of Web-based Geographic Information System in South Batang Alai which consists of (i) job progress data, (ii) inventory data (iii) realization data and (iv) map of irrigation areas that can be accessed online to enable users to see network positions irrigation in detail. This website is designed using a dynamic display using the programming language PHP and MySQL as database processing and using an online system provided that the device must be connected to the internet network. Keywords: Irrigation, Batang Alai, PHP, MySQL, Webgis.